Clinicopathological and prognostic significance of heat shock proteins in hepatocellular carcinoma: a systematic review and meta-analysis - Xiang, Dan; Jiang, Mengdan; Chen, Ya; Liu, Chengjiang; Li, Leilei (Frontiers in Oncology, 2023)
Background: Overexpression of heat shock proteins (HSPs) has been observed in a wide range of human tumors, and there is an increasing evidence demonstrated that HSPs play a key role in tumor progression. Several studies were conducted to explore the clinicopathological characteristics and prognostic value of HSPs in hepatocellular carcinoma (HCC), but the results remain controversial. To address this gap, we conducted a systematic review and meta-analysis.The eligible literature was obtained from PubMed, Cochrane library, Web of science, Embase, Chinese National Knowledge Infrastructure and Wan Fang databases. We used the odds ratio (OR) and hazard ratio (HR) as the suitable parameters to assess the clinicopathological features and prognostic value of HSPs in HCC patients.The meta-analysis results showed that HSPs expression was associated with overall survival (OS) of HCC patients (HR = 1.61, 95%CI = 1.22-2.13, P=0.001, I 2 = 62.7%). In addition, the pooled results suggested that HSPs expression was significantly correlated with tumor differentiation (OR = 1.33, 95%CI = 1.08-1.65, P = 0.907), vascular invasion (OR = 1.31, 95%CI = 1.02-1.69, P = 0.921) and lymphatic metastasis (OR=1.98, 95%CI= 1.70-2.31, P = 0.740). Meanwhile, the subgroup analysis showed a significant correlation between the expression of HSP27 (HR=1.69, 95%CI = 1.24-2.31, P = 0.674) and HSP90α (HR=2.03, 95%CI = 1.73-2.40, P = 0.743) with OS of HCC patients.Our meta-analysis confirms that HSPs expression is closely associated with a worse prognosis in HCC patients, and may be directly involved in tumor differentiation and distant metastasis. In addition, the subgroup analysis results demonstrate that the expression of HSP27 and HSP90α can be served as potential prognostic predictors of HCC.